Arranging Food Security in Central Papua: Urgency of Regulation in Responding to the High Prevalence of Insufficient Food Consumption in the Expansion Region - NOVEMYANTO, ALFIN DWI (Journal of Indonesian Rural and Regional Government, 2025)
As a new expansion region, Central Papua Province faces serious challenges in providing the right to food, with the highest Prevalence of Insufficient Food Consumption (PKPK) nationally, which is 37.69% in 2024. This study examines the urgency of establishing food security regulations in Central Papua to guarantee the constitutional right to food and realize social justice. The method used is normative legal research with a regulatory and conceptual approach based on John Rawls’ social justice theory. The results of the study indicate that there is no substantive legal gap in regulating food security at the regional level, which has an impact on weak cross-sectoral coordination and marginalization of vulnerable groups, primarily indigenous peoples. The novelty of this study lies in the emphasis on using PKPK indicators as the basis for formulating data-based and participatory regulations. This study introduces the strengthening of the role of law as an instrument of social engineering, which not only regulates technically but also emphasizes the state’s responsibility in providing fundamental citizen rights. Establishing the Regional Regulation/Provincial Regulation on Food Security in Central Papua is an urgent constitutional step to realize fair, measurable, and sustainable food governance in the new autonomous region.